Experimental investigation on self-sustained smouldering of food-processing sludge with extremely high moisture content: From laboratory-scale to pilot-scale volumetric scale-up. (1st March 2023) - Ma, Lun; Yan, Chao; Feng, Chao; Qiao, Yu; Huang, Jingchun; Fang, Qingyan; Zhang, Cheng
Highlights: Food-processing sludge with extremely high moisture is treated by smouldering. Sand: Food-processing sludge: Sawdust = 25:5:1 may be a reasonable mixing ratio. Continuous self-sustaining smoldering is volumetrically scaled up to the pilot-scale. O2, CO, NO x, SO2, VOC, and dioxin concentrations of flue gas are measured. Heavy metal element is low in ash, good self-healing of smouldering is validated. Abstract: Although smouldering of solid waste with high moisture has shown strong promise in laboratory studies, there are fewer reports about the larger-scale device and continuous operation. This work studies a self-sustaining smouldering treatment of food-processing sludge (FPS) with extremely high moisture (over 85 %) in laboratory- and pilot-scale devices. Results from laboratory-scale experiments show that adding auxiliary fuel is necessary to maintain FPS self-sustaining smouldering, Sand: FPS: Sawdust = 25:5:1 is a reasonable mixing ratio. Then, the self-sustaining smouldering is volumetrically scaled up to the pilot-scale. The smouldering asynchrony in the feedstock is observed due to the non-uniform air flux. Compared to the laboratory-scale, the pilot-scale device presents a similar temperature level but a higher smouldering velocity. Furthermore, a continuous process in the pilot-scale device is successfully performed, and the flue gas concentrations are measured: 15.0 ∼ 16.5 % for O2, 4000 ∼ 5500 ppm for CO, 155 ∼ 195 ppm for NO x, 210 ∼ 250 ppm for VOCs, 55 ∼ 70 ppm for SO2, 0.0138 ∼ 0.0317 ngTEQ/m 3 (at 11 % O2 ) for dioxin. These studied results can provide useful information for continuous, low-energy solid waste treatment.